Application of Herbicide to Manage Weed Flora in Blackgram - Malviya , Shreya (Emerging Issues in Agricultural Sciences Vol. 9, 2023)
Blackgram, scientifically known as Vigna mungo, holds a significant place in Indian agriculture and cuisine. India is one of the world's leading producers of blackgram, playing a vital role in fulfilling both domestic consumption and export demands. The yield of blackgram, a significant pulse crop in India, is influenced by a multitude of interconnected factors that collectively shape its production outcomes. Weed infestation poses a significant challenge to the yield of blackgram, an important leguminous crop. Weeds not only hinder the crop's access to vital resources but also create favorable conditions for pests and diseases, further compromising yield potential. Effective weed management practices are crucial to mitigate these negative effects. Present chapter describes the management of weeds using herbicides. The study concluded that the Echinochloacolona (29.39%) and Dinebraretroflexa (24.30%) were predominant weeds in blackgram. Further, the post emergence application of propaquizafop+imazethapyr mixture from 53+80 was found the suitable for effective control of composite weed flora associated with blackgram in central India.